2018
DOI: 10.1039/c8nj00747k
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying conventional C–H⋯π(aryl) and unconventional C–H⋯π(chelate) interactions in dinuclear Cu(ii) complexes: experimental observations, Hirshfeld surface and theoretical DFT study

Abstract: Conventional C–H⋯π(aryl) and unconventional C–H⋯π(chelate) interactions are explored in detail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(19 citation statements)
references
References 70 publications
0
19
0
Order By: Relevance
“…Recent investigations have suggested that these types of interactions are responsible in the stabilisation of inorganic and hybrid metal-organic compounds. [26][27][28][29] In this work we have demonstrated the relevance of C-H?p(CR) in the crystal packing of the [Cu(DZP) 2 ]Á2H 2 O metal complex.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Recent investigations have suggested that these types of interactions are responsible in the stabilisation of inorganic and hybrid metal-organic compounds. [26][27][28][29] In this work we have demonstrated the relevance of C-H?p(CR) in the crystal packing of the [Cu(DZP) 2 ]Á2H 2 O metal complex.…”
Section: Introductionmentioning
confidence: 70%
“…Recently, numerous investigations reported evidence of C-H?p and p-stacking interactions with the p-cloud of a six-membered chelate ring due to the planarity and delocalisation of the p-system. [27][28][29] Also, there are intermolecular C-H?p interactions (C11-H11A?Cg2 ¼ 3.875 Å ), where Cg2 is the ring centroid defined by atoms C1-C6 (see Fig. S6, Supplementary Material).…”
Section: The [Cu(dzp) 2 ] Crystal Structure Is Further Stabilised By mentioning
confidence: 99%
“…Where, d e and d i are the distances from the point to the nearest nucleus external and internal to the surface respectively; r i vdw and r e vdw are the internal and external van der Walls (vdW) radii of the two atoms to the surface respectively. The 2D fingerprint plot displays the summary of available contacts in the crystal [42][43][44][45][46] that are generated by binning (d e , d i ) pairs in the interval of 0.01 Å. The 2D histogram was produced as a function of the fraction of surface points in that bin (essentially a pixel) that varies from few points to many points i.e., from blue through green to red.…”
Section: Hirshfeld Surface Analysismentioning
confidence: 99%
“…Non-covalent interactions such as hydrogen bonds, halogen bonds, CH •••π and π•••π interactions play important roles in chemical, catalytic, photochemical, crystal engineering, and supramolecular processes (1)(2)(3)(4). Particularly, hydrogen bonding interactions such as the O⋯H and N ... H interactions lead to an increase in the stability of crystal packaging (5). Van der Waals interactions also play a key role in the formation of the supramolecular structures.…”
Section: Introductionmentioning
confidence: 99%